April and Esme, tooth fairies - Graham, Bob, 1942- (Somerville, Mass. : Candlewick Press, 2010)
On their first assignment, two young tooth fairy sisters journey by night into the huge world of humans to collect Daniel Dangerfield's tooth and fly it safely home.
"A Junior Library Guild selection"--Jkt.
Keywords: Fairies -- Juvenile fiction; Sisters -- Juvenile fiction; Fairies -- Fiction; Sisters -- Fiction; Lost teeth -- Fiction; Magic -- Fiction; Seven-year-old girls -- Fiction; Girls -- Fiction